Serum OX40 Ligand as a Biochemical Regulator of Th2-Dominant Immune Activation in Asthma: An Integrated Cytokine Network Analysis: Serum OX40L and Immune Activation in Asthma - Zhu, Ziyi; Li, Shumin (Journal of Medical Biochemistry, 2026)
Background: Asthma is characterized by complex immune dysregulation involving coordinated cytokine and chemokine networks. OX40 ligand (OX40L), a key T-cell co-stimulatory molecule, has been implicated in Th2-mediated inflammation; however, its serum-level biochemical interactions with immune activation pathways in asthma remain incompletely defined. Methods: In this cross-sectional study, serum OX40L and immune activation-related factors were quantified in 82 patients with asthma and 40 healthy controls. Multiplex cytokine analysis was performed to measure Th2-, Th17-, pro- and anti-inflammatory mediators, along with chemokines and total IgE. Lung function indices were assessed by spirometry. Correlation analysis and multivariable linear regression were applied to identify immune factors independently associated with serum OX40L levels. Results: Serum OX40L concentrations were significantly elevated in asthma patients compared with controls and increased progressively with disease severity (all P<0.001). OX40L exhibited strong positive correlations with Th2-associated cytokines, particularly interleukin-5 (IL-5; r=0.75, P<0.001), and chemokines, while showing a significant inverse association with the anti-inflammatory cytokine IL-10. OX40L levels were also negatively correlated with forced expiratory volume in one second (FEV1%pred; r=-0.72, P<0.001). Multivariable regression identified IL-5 (β=0.35), FEV1%pred (β=-0.28), and annual exacerbation frequency (β=0.22) as independent biochemical determinants of serum OX40L, collectively explaining 68.3% of its variance. Conclusion: Serum OX40L is closely integrated within the Th2-dominant immune activation network in asthma and reflects both immune imbalance and functional airway impairment. These findings support OX40L as a biochemically relevant indicator of immune activation intensity and highlight its potential role within cytokine-driven regulatory pathways in asthma.